Human neutrophil elastase inhibitory potential of flavonoids from Campylotropis hirtella and their kinetics. (1st November 2016) - Tan, Xue Fei; Kim, Dae Wook; Song, Yeong Hun; Kim, Jeong Yoon; Yuk, Heung Joo; Wang, Yan; Curtis-Long, Marcus J.; Park, Ki Hun
Abstract: Campylotropis hirtella is used as a food supplement in the subtropical region of China. In an intensive hunt for human neutrophil elastase inhibitors, we isolated eight flavonoids from C. hirtella three of which (1 –3 ) emerged to be elastase inhibitors. Geranylated flavonoids (1 –3 ) displayed significant inhibitory activity with IC50 s between 8.5 and 30.8 μM. The most striking example was geranylated isofavanone3 that inhibited elastase significantly (IC50 = 30.8 μM) but its parent compound (dalbergioidin) and isoflavone analog (5 ) were inactive (IC50 > 200 μM). Compounds (1 –3 ) displayed different kinetic mechanisms (noncompetitive, competitive, and mixed type, respectively) that were dependent upon the parent skeleton. The competitive inhibitor, isoflavan-3-ol-4-one2 manifested an inhibition of isomerization profile for elastase with kinetic parameters K 5 = 0.0386 M −1 S −1, K 6 = 0.0244 μM −1 S −1 and K i app = 16.3427 μM. The specific identification of metabolites was accomplished by LC-DAD-ESI/MS that was also used to analyze abundance of active components (1 –3 ) within the plant.